Pore-scale simulation of remaining oil distribution in 3D porous media affected by wettability and capillarity based on volume of fluid method - Yang, Yongfei; Cai, Shaobin; Yao, Jun; Zhong, Junjie; Zhang, Kai; Song, Wenhui; Zhang, Lei; Sun, Hai; Lisitsa, Vadim (International journal of multiphase flow, 2021)
•Direct pore-scale modelling of two-phase flow in three-dimensional porous media by VOF method.•The evolution of remaining oil was investigated by considering wettability, viscous force and capillary number.•Phase circulation phenomenon was simulated and two circulation patterns were found which can be interconverted.•Preferred conditions for improving the oil recovery rate was discussed in detail. Characterizing the trapped phase in porous media is essential for many engineering applications, such as enhanced oil recovery, nuclear storage, and geological sequestration of CO2. This study aims to study the distribution, evolution, and influencing factors of the remaining oil in the process of water flooding at the pore scale. The single-connected pore space model was established by reconstructing the real micron CT scanned images of carbonate rocks. The VOF (volume of fluid) method using FSF (filtered surface force) formulation was adopted on OpenFOAM platform to simulate the oil-water two-phase flow process at the pore scale. Different wettability and capillary number were considered in the model. The accuracy of the model was proved by comparing with previous experimental results. The results showed that in the process of water flooding, the complex pore structure would lead to the generation of remaining oil, and the phase circulation phenomenon can be observed in the remaining oil and presents two distribution forms: co-current driven flow and lid-cavity driven flow. It also revealed that the phase recirculation increases the viscous dissipation. Further research also showed that the two forms of recirculation could be transferred by changing the wettability and that a higher capillary number was more beneficial for reducing the remaining oil saturation.